Transforming of Construction Contract Administration: Data Warehouse Modeling - Chong, Heap Yih; Zin, R. (Advanced Institute of Convergence I T, 2011)
Construction stakeholders always use standard form of contract to regulate their contractual obligations and expectations during contract administration process. They need to refer a vast of contract provisions in the process. It always leads misunderstanding and interpretation errors as most of construction practitioners are without a proper legal background. Hence the research aims to apply data warehouse technology to assist end-users for better and/or right decision making. A conceptual model of data warehouse for contract administration is developed and verified by twelve reputed experts in the construction industry. The results show that the data warehouse modeling is feasible and practical to the construction practitioners. It would render a more effective and proactive approach in contract administration towards dispute resolution or prevention.